A Life Cycle Assessment study of iron ore mining. - Ferreira, Hélio (2015)
This paper assessed the cradle-to-gate life cycle of an iron ore mining. The study was based on production data from an open pit mine located in the Iron Quadrangle/Brazil. The functional unit was defined as “one tonne of iron ore concentrate produced” and the data used were collected directly from the company's production reports covering the time of one year. The evaluation included the classification and characterization of life cycle impacts, not including normalization and weighting as well as sensitivity analysis of results. The evaluation of impacts used SimaPro-7, Ecoinvent 2.0, Eco indicator'99 and IPCC 2007. The results indicated that the use of grinding media in the processes is the main source of environmental impacts in the iron ore production chain, highlighting its contribution to life cycle impacts on human health and quality of ecosystems. Ore transportation by conveyor belts powered by electricity was more efficient in relation to the generation of impacts on the abiotic resources depletion and on climate changes than ore transportation by diesel trucks because the electricity generation matrix in Brazil has significant participation from hydroelectric plants.